The effect of several kinds of baits and moon phases on the catch of mangrove crab (Scylla serrata) with trap - Kaim, Mukhlis A; Reppie, Emil; Budiman, Johnny (AQUATIC SCIENCE & MANAGEMENT, 2013)
Trap is one of the common fishing gears used by the fishermen to catch mangrove crabs. Using several kinds of bait could increase the fishing power of the traps. The objective of this research was to study experimentally the effect of several kinds of trap baits and moon phases toward the capture of mangrove crab. Catch data were collected using 12 units of traps,which operated in the estuary waters of Kalurae Village, Regency of Sangihe Islands. Four kinds of bait were used to trap: scads mackerel (Decapterus macarellus), little tuna (Euthynnus sp.), trevally(Caranx sp.) and chicken innards. Data were analyzed by randomized block design. Analysis of variance showed that different types of bait on the trap and moon phase caused highly significant effect on catch. Least significant differences test showed that using scads mackerel bait on the trap was not significantly different from little tuna bait, but differed significantly from trevally and chicken innards baits. Similarly, using little tuna bait was not significantly different from trevally bait, but differed significantly from chicken innards bait; and trevally bait was not different from chicken innards bait. Catching mangrove crabs with traps should use scads mackerel and little tuna baits, and be operated around the new moon phase© Bubu merupakan alat tangkap yang umum digunakan nelayan untuk menangkap kepiting bakau. Penggunaan beberapa jenis umpan, diduga dapat meningkatkan fishing power dari alat tangkap bubu. Penelitian ini bertujuan mempelajari pengaruh jenis umpan bubu dan fase umur bulan di langit terhadap hasil tangkapan kepiting bakau; dikerjakan dengan metode eksperimental. Data tangkapan dikumpulkan dengan mengoperasikan 12 unit bubu, di perairan estuari Kampung Kalurae, Kabupaten Kepulauan Sangihe. Empat jenis umpan yang diperlakukan, yaitu ikan layang (Decapterus macarellus), tongkol (Euthynnus sp.), selar (Caranx sp.) dan jeroan ayam. Data dianalisis berdasarkan Rancangan Acak Kelompok. Analisis Sidik Ragam menunjukkan bahwa perbedaan jenis umpan pada bubu dan fase umur bulan berpengaruh sangat nyata terhadap hasil tangkapan. Uji Beda Nyata Terkecil menyatakan bahwa penggunaan jenis umpan layang pada bubu tidak berbeda nyata dengan umpan tongkol, tetapi berbeda sangat nyata dengan penggunaan umpan selar dan umpan jeroan. Demikian juga penggunaan umpan tongkol tidak berbeda nyata dengan umpan selar, tetapi berbeda sangat nyata dengan umpan jeroan; sedangkan penggunaan antara umpan selar dan jeroan tidak ada perbedaan yang nyata. Umpan ikan layang dan ikan tongkol serta fase umur bulan I dan fase IV memberikan hasil tangkapan kepiting bakau yang lebih baik©